2005
DOI: 10.4269/ajtmh.2005.73.1016
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis and Typing of Trypanosoma Cruzi Populations and Lineages in Cerebral Chagas Disease in a Patient With Aids

Abstract: Trypanosoma cruzi DNA was amplified from an intracranial biopsy and peripheral blood of an HIV patient with encephalitis; this episode was indicative of AIDS and congenital Chagas disease. The analysis of a micro-satellite locus revealed a multiclonal parasite population at the brain lesion with a more complex minicircle signature than that profiled in blood using restriction fragment length polymorphism (RFLP)-PCR and low stringency single primer (LSSP) PCR. Interestingly, different sublineages of T. cruzi II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 15 publications
4
63
0
9
Order By: Relevance
“…In our study, the two human isolates identified were typed as TC IId. Given that T. cruzi natural populations display different tissue tropism in mammalian hosts (Macedo et al, 2004;Burgos et al, 2005Burgos et al, , 2008 we cannot reject the possibility that TC IIe can also cause human infection and disease despite displaying low degrees of parasitemia as determined by xenodiagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the two human isolates identified were typed as TC IId. Given that T. cruzi natural populations display different tissue tropism in mammalian hosts (Macedo et al, 2004;Burgos et al, 2005Burgos et al, , 2008 we cannot reject the possibility that TC IIe can also cause human infection and disease despite displaying low degrees of parasitemia as determined by xenodiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Infections with T. cruzi were confirmed by kDNA-PCR amplification of the 330 bp fragment from the minicircle DNA of the kinetoplastid genome using primers and cycling conditions published previously (Schijman et al, 2003, Burgos et al, 2005. PCR tests were carried out under conditions that prevented DNA contamination.…”
Section: Pcrmentioning
confidence: 99%
“…The occurrence of mixed infections of T. cruzi DTUs in mammalian hosts might be masked by genotype selection associated with specific culture methods, 52 the sensitivity of PCRs used to identify parasite genotypes, and differential parasite histotropism. 53 The ongoing accelerated deforestation of the Gran Chaco (including our study area) has led to fragmented forest patches that may increase the contact rates between sylvatic or domestic hosts of T. cruzi and triatomine bug species. Residual forest fragments act as a refuge for some host species.…”
Section: Discussionmentioning
confidence: 99%
“…48 Studies showing the impact of this genetic variability on HIV coinfection are scarce. These studies 49,50 have suggested a differential tissue tropism of the infecting DTUs and have reported mixed infections in coinfected patients, observing TcI and TcII-or TcI, TcV, and TcVI-in the blood, heart, and brain tissue of Chagas disease patients with HIV/AIDS coinfection with cardiomyopathy and encephalopathy. Among immunocompetent patients, Chagas disease can be present as an acute manifestation, but chronic forms are diagnosed more frequently.…”
Section: Chagas Diseasementioning
confidence: 99%